Association Between Gut Microbiome and Major Depressive Disorder, Bipolar Disorder and Schizophrenia: A Systematic Review - Rangraze, Imran; Khan, Shehla Shafi; wali, Adil Farooq; Menezes, Godfred; Goud, Manjunatha; Jabran, Muhammad (Migration Letters, 2023)
Background: Gut bacteria have been shown to disrupt homeostatic balance and influence the pathophysiology of a broad variety of psychological diseases, even though they play a significant role in normal health maintenance. It has long been assumed that the gut microbiota plays a crucial role in the pathophysiology of major depression disorder (MDD), bipolar disorder (BD), and schizophrenia (SZ). A definite cause-and-effect connection has not, however, been demonstrated. Microbial dysbiosis, which is linked to MDD, BD and SZ is characterised as an imbalance in microbial diversity brought on by the disruption of the microbiota’s delicate balance and the ensuing psychological abnormalities. Therefore, we recently conducted a systematic review of the observational literature comparing the composition of gut microbiota in persons with MDD, SZ, BD with healthy controls. Methods: This review was written according to the guidelines established by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Pubmed, Scopus, Embase, Web of Science, Ovid, Global Health, PsycINFO, etc. were searched thoroughly using the phrases “gut microbiota, psychological disorders, composition, major depressive disorder, bipolar disorders, schizophrenia, etc.” Results: For this comprehensive assessment, 26 articles were chosen. Our analysis showed an increase in lactic acid-producing bacteria in all three psychological disorders (MDD, BD, and SZ). Cases of the three psychological disorders had a greater prevalence of the genus Lactobacillus. Other lactic acid manufacturers, such as Enterococcus and Streptococcus and Bifidobacterium were also observed to be more abundant in patients with MDD, BD, SZ respectively. Our analysis also revealed that all three psychological disorders shared an increase in the abundance of bacteria involved in the metabolism of glutamate and aminobutyric acid (GABA). It was observed that number of butyrate producing gut microbiota was lower in these psychological disorders. Conclusion: There was a general trend toward increased abundances of bacteria involved in glutamate and GABA metabolism, and lower abundances of butyrate-producing bacteria in psychological disorders namely MDD, BD and SZ.